Functional Characterization of Alternative and Classical Pathway C3/C5 Convertase Activity and Inhibition Using Purified Models - Zwarthoff, Seline A.; Berends, Evelien T. M.; Mol, Sanne; Ruyken, Maartje; Aerts, Piet C.; Józsi, Mihály; de Haas, Carla J. C.; Rooijakkers, Suzan H. M.; Gorham, Ronald D. (Frontiers in Immunology, 2018)
Complement is essential for the protection against infections; however, dysregulation of complement activation can cause onset and progression of numerous inflammatory diseases. Convertase enzymes play a central role in complement activation and produce the key mediators of complement: C3 convertases cleave C3 to generate chemoattractant C3a and label target cells with C3b, which promotes phagocytosis; C5 convertases cleave C5 into chemoattractant C5a, and C5b, which drives formation of the membrane attack complex. Since convertases mediate nearly all complement effector functions, they are ideal targets for therapeutic complement inhibition. A unique feature of convertases is their covalent attachment to target cells, which effectively confines complement activation to the cell surface. However, surface localization precludes detailed analysis of convertase activation and inhibition. In our previous work, we developed a model system to form purified alternative pathway C5 convertases on C3b-coated beads and quantify C5 conversion via functional analysis of released C5a. Here, we developed a C3aR cell reporter system that enables functional discrimination between C3 and C5 convertases. By regulating the C3b density on the bead surface, we observe that high C3b densities are important for conversion of C5, but not C3, by alternative pathway (AP) convertases. Screening of well-characterized complement-binding molecules revealed that differential inhibition of AP C3 convertases (C3bBb) and C5 convertases (C3bBb(C3b)n) is possible. Although both convertases contain C3b, the C3b-binding molecules Efb-C/Ecb and FHR5 specifically inhibit C5 conversion. Furthermore, using a newly-developed classical pathway convertase model, we show that these C3b-binding proteins not only block AP C3/C5 convertases, but also inhibit formation of a functional classical pathway C5 convertase under well-defined conditions. Our models enable functional characterization of purified convertase enzymes and provide a platform for the identification and development of specific convertase inhibitors for treatment of complement-mediated disorders.